Implementation of a Mobile Application for GPS-Based Reporting of Water Pollution and Invasive Species - Muchammad Hasbi Ashshiddiqi; Muhammad Fahrie (Komunitas Dosen Indonesia, 2025)
Water pollution and the spread of invasive species threaten Indonesian river ecosystems, yet public participation in monitoring remains limited, often due to the lack of a centralized and accessible reporting tool. This study develops and validates a mobile platform to address this gap. Its primary contribution is a novel dual-reporting model, allowing the public to report both pollution incidents and invasive species findings using a single GPS-based application. This integrated approach provides a more holistic dataset than single-issue tools, critically enabling the future analysis of ecological links between pollution hotspots and invasive species outbreaks. The application was developed using Flutter for cross-platform accessibility and Supabase as a Backend as a Service to ensure scalability and rapid development. The main finding, confirmed through Black Box testing, is a functional prototype where all core user-side features, such as registration, login, and GPS report submission, performed successfully. This outcome validates the system's technical feasibility and the practical viability of using non-experts for data collection. While user-side functionality is proven, the report management functionality for administrators remains in the early stages. This research provides a viable tool for agencies to gather real-time field data. It also supports future development focused on a comprehensive admin dashboard, which is essential for report validation, data aggregation, and trend analysis, ultimately enhancing the system's effectiveness.